Deteksi Katarak Pada Mata Menggunakan Image Processing (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2023)
The eyes are one of the most important organs in the human body. Without eyes, we would not be able to see the objects around us. There are several eye diseases that are quite dangerous. One of the most dangerous eye diseases is cataracts. A cataract is an eye disease that causes clouding of the lens of the eye. In general, cataracts in the eye will develop slowly and, initially, are not too bothersome. But over time, it will interfere with vision and cause blindness. Therefore, cataracts must be treated immediately before they are fatal to the patient. Cataract is one of the most common causes of blindness in Indonesia. The results of the Rapid Assessment of Avoidable Blindness (RAAB) survey by the Association of Indonesian Ophthalmologists (Perdami) and Balitbangkes in 15 provinces, namely West Sumatra, North Sumatra, South Sumatra, DKI Jakarta, West Java, Central Java, East Java, South Kalimantan, Bali, NTT, NTB, North Sulawesi, South Sulawesi, Maluku, and Papua with the target population over 50 years old, the blindness rate is known to reach 3 percent. Cataract is the leading cause, accounting for approximately 81 percent [1]. Based on these problems, the author took the initiative to create a program to detect cataracts in the eye using Image Processing.